Guerilla war against the Japanese Americans in the Visayas - Ignacio, Violeta S. (2010)
Like the American guerrillas in other regions of the Philippines, most American guerrillas in the Visayas were escapees and evaders of Japanese captivity. Others were civilians displaced from jobs. Outstanding among them were James M. Cushing, miner, and Harry Fenton, radio announcer, who led the guerrillas in Cebu. Others would perform combat missions, coast watching, radio operation, training and organization of guerrillas, intelligence, counter-propaganda, supply and engineering services, and other errands for Filipino and American guerrilla leaders. The performance of these tasks involved adventures, exciting everyday life, and problems of survival. Eventually, some of them would be rescued by U.S. submarines, others would continue resistance and render services to the American reoccupation forces. The American coast watcher reports would alert the U.S. Navy of the impending Japanese attack in the Battle for the Philippine Sea. Although the American guerrillas in the Visayas had their share of tragedy, they were blessed by luck in finding the "Koga papers" - the Japanese defense plan of the Southwest Pacific Area that revealed Leyte as weakly defended. This intelligence information changed the initial U.S. invasion plan of the Philippines from Mindanao to Leyte. This singular accomplishment of the American and Filipino guerrillas hastened the retaking of the Philippines and contributed to the victory of the Filipino and American forces against Japan in the Visayas.